Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1159/000320954
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Malignancy from Thyroid Nodular Disease as an Element of Clinical Management of Patients with Hashimoto’s Thyroiditis

Abstract: Background: Many studies have investigated the association between chronic lymphocytic thyroiditis (CLT) and papillary thyroid carcinoma (PTC), but clinical management of this condition has never been addressed specifically, even in recent guidelines. Surprisingly the likelihood of a nodule as being cancerous in a CLT has never been explicitly expressed in terms of relative risk. Methods: This study was based on a retrospective analysis of 404 patients undergoing total thyroidectomy. Results: Sixty-nine patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
1
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(33 citation statements)
references
References 21 publications
(19 reference statements)
2
27
1
2
Order By: Relevance
“…A total of 38 articles satisfied the eligibility criteria (3,4,5,6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40). The eligible studies consisted of 37 case-control studies and one cohort study, all of which were hospital based.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…A total of 38 articles satisfied the eligibility criteria (3,4,5,6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40). The eligible studies consisted of 37 case-control studies and one cohort study, all of which were hospital based.…”
Section: Resultsmentioning
confidence: 99%
“…Loh et al (18) and Yoon et al (24) reported that PTC with HT was significantly associated with females and a lower incidence of extrathyroidal invasion and lymph node metastasis. Several studies found that PTC with HT had a tendency for multifocal involvement (3,4,26,34). In contrast, other studies failed to present any significant clinicopathologic characteristics in PTC with HT (5,25,40).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations